Sago Product Diversification, Sales Volume And Business Feasibility Of Sawa Bioindustry - Seprilia M Kailuhu; Natelda R. Timisela; Johanna M. Luhukay (Cita konsultindo, 2023)
This study aims to describe product diversification, determine the volume of sales and the business feasibility of processing sago bioindustry products from SAWA Waraka Negeri. The results showed that there are 3 types of diversification carried out by the bioindustry, namely product diversification which produces 3 types of processed sago products, namely sago flour, sago noodles and sago rice, price diversification which results in 2 types of prices, namely Rp. . 20,000 for the size of kg or 250 grams specifically for sago noodles and Rp. 40,000 for 1kg or 500 grams for sago noodles, and packaging diversification based on size, namely kg and 1kg packages. The packaging used is a stand pouch which is equipped with a label or sticker for SAWA bioindustry. And based on the results of the feasibility analysis of the SAWA bioindustry for the three products,